2018
DOI: 10.3390/ijerph15061248
|View full text |Cite
|
Sign up to set email alerts
|

Residential Greenness and Birthweight in the State of Massachusetts, USA

Abstract: Natural vegetation, or greenness, may benefit maternal health and consequently, fetal growth, by providing opportunities for physical activity and psychological restoration, and decreasing detrimental environmental exposures. We retrieved Massachusetts Birth Registry data from 2001–2013 and investigated the association between residential greenness and birthweight in full-term births (≥37 weeks gestation). We calculated average residential greenness during pregnancy using 250 m normalized difference vegetation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 42 publications
4
39
1
Order By: Relevance
“…211 A study by the same team in Texas found that for all urban areas in Texas, there was a small increase in term birthweights across quartiles of NDVI (compared with the lowest). 235 As with the studies by Fong et al 236 and Agay-Shay et al 233 , this study found that comparing the 2 nd and 3 rd quartiles of exposure to the lowest quantile has a stronger effect than comparing the 4 th . When stratifying by four major cities, quite different results per city were seen.…”
supporting
confidence: 77%
See 4 more Smart Citations
“…211 A study by the same team in Texas found that for all urban areas in Texas, there was a small increase in term birthweights across quartiles of NDVI (compared with the lowest). 235 As with the studies by Fong et al 236 and Agay-Shay et al 233 , this study found that comparing the 2 nd and 3 rd quartiles of exposure to the lowest quantile has a stronger effect than comparing the 4 th . When stratifying by four major cities, quite different results per city were seen.…”
supporting
confidence: 77%
“…Some of the papers in this review point to a nonlinear response to green space, with the highest values not necessarily those that predict the best gains in birthweight. 233,236 These papers indicate that a proportion of green space in the zone of 25-75% may have the strongest influence on birthweight. I was not able to find studies to support or refute this finding across the health literature, and thus suggest that future studies consider whether there is a threshold level for the benefits of green space and test whether green space acts in a linear fashion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations